Experimental improvement of the technology of cutting of high-pressure hoses with metal braid on hand cutting machine - Karpenko, Mykola; Bogdevicius, Marijonas; Prentkovskis, Olegas (Publishing House of Lviv Polytechnic National University, 2016)
In the article the review of the problem of improvement of technology of high pressure hoses cutting on the hand cutting machines is analyzed. Different methods of cutting of high pressure hoses into the billets are overviewed and the quality of edge cuts of hoses is analyzed. The comparison of treatment on automatic cutting machines and on hand cutting machines is carried out. Different experimental techniques of improvement of the quality of edges cutting of high pressure hoses are presented. On the basis of experimental method, a new cutting technology which consists in maximally close fixation of high pressure hoses to the cutting disc is proposed. In the basic design of the hand cutting machine, the only supports are provided, so that the cutting of the edge section of high pressure hoses causes the metal braid loosening. The proposed technology excludes the scrolling and bending of high pressure hoses during cutting, so that the loosening of metal braid is also excluded. In the paper it is shown that the scheme of distribution of cutting forces during the cutting of high pressure hoses is presented and the mathematical model of determination of normal and tangential cutting forces is formed. With a help of tensiometric table the values of components of cutting forces during free and fixed cutting of high pressure hoses were defined and their comparison was performed. As a result of the use of this technology the edges of the cut off high pressure hoses meet the necessary requirements without using of complicated technological processes.
Keywords: high pressure hose; metal braid; cutting force; hand cutting machine; tensiometric table; technological process; loosening